IMPACT OF MACROECONOMIC INDICATORS ON MSME CREDIT GROWTH: PATHWAYS FOR THE FUTURE OUTLOOK AND ITS IMPACT DURING ECONOMIC SLOWDOWN IN INDIA - Vishal Tripathy; Dr. Sanchita Som; Qristin Violinda (International Educational Journal of Science and Engineering, 2026)
The paper aims to study the impact of macroeconomic variables- GDP growth rate and IIP growth rate on Credit growth rate of MSME sector in India. It focuses on predicting the credit growth rate values based on historical data from March’2019 to March’23 on a quarterly basis using Multiple Linear Regression technique. Then we have forecasted the macroeconomic variables from June’23 to March’26 by taking a weighted factor from the growth rate pattern of 2021-22 and 2022-23 using Macroeconomic variable forecasting technique. Then-after we have forecasted the Credit growth rate values from June’23 to March’26 based on forecasted values of macroeconomic variables using Time Series Forecasting technique (White-Noise Model). Finally, we have conducted scenario analysis where we have tried to analyse the decrease in credit growth rate in MSME sector during an economic slowdown in India, i.e when GDP growth rate & IIP growth rate together falls by 7% & 1% (Low severity level); 10% & 5% (Medium severity level); 15% & 7% (High severity level).